TANGGUNG JAWAB MORAL INSINYUR SIPIL TERHADAP KESELAMATAN PENGGUNA INFRASTRUKTUR - Edison Hatoguan Manurung; Angga Febriadi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Infrastructure user safety is a fundamental aspect of civil engineering practice that is closely related not only to technical compliance but also to engineers' moral responsibility toward society. This study aims to analyze the forms, scope, and implications of civil engineers’ moral responsibility in ensuring infrastructure user safety and to identify factors influencing the implementation of professional ethical principles in engineering decision-making. The research employed a quantitative approach using a narrative review method. Data were collected from 35 scientific articles, professional standards, and policy documents published between 2020 and 2025. A data extraction form was used to identify indicators of moral responsibility, ethical compliance, and infrastructure safety. Data analysis was conducted using descriptive quantitative techniques, including frequency, percentage, correlation, and trend analysis. The findings reveal that 88.57% of the reviewed literature identified public safety as the primary priority of civil engineers’ professional responsibility. Furthermore, 82.86% of the sources indicated that ethical violations contribute to an increased risk of infrastructure failure, while 80.00% emphasized the importance of moral responsibility in engineering decision-making. Correlation analysis demonstrated a strong positive relationship between moral responsibility and infrastructure user safety (r = 0.812; p < 0.05). The study concludes that moral responsibility is an essential component of civil engineering practice and plays a significant role in protecting infrastructure users. The findings contribute to the development of engineering ethics theory, public safety policies, and the improvement of civil engineering practices oriented toward public welfare.